The Role of Art and Music Interventions in Mediating Emotional Regulation and Reducing Academic Stress among University Students - Muqaffi; Popy Mayasari Afendy; Nadia Aulia Nadhirah; Ilfiandra; Juntika Nurihsan; Ipah Saripah; Sudaryat Nurdin Akhmad; Dody Hartanto (Advances in Psychological Sciences and Applications, 2026)
Academic stress is a common issue experienced by university students and is closely associated with mental health conditions and a decline in academic performance. Emotion regulation plays a crucial role in stress management and has been proven to be an adaptive ability that enhances well-being. Interventions involving arts and music have increasingly been explored as effective approaches to improving emotion regulation skills among university students. This paper aims to systematically review existing studies related to Arts and music-based interventions in enhancing emotion regulation and reducing academic stress among university students, as well as to identify the intervention methods implemented. The method used in this paper is a systematic review of experimental studies, meta-analyses, and qualitative research focusing on arts and music interventions among university students. The analysis of results is based on measurements of academic stress, emotion regulation, and psychological well-being. The main findings indicate that Arts and music-based interventions consistently reduce academic stress levels and help improve students’ emotion regulation skills. In conclusion, Arts and music-based interventions are effective in enhancing emotion regulation and reducing academic stress among university students. Such approaches can be integrated into mental health support programs, including counseling and group guidance services, for students at the university level.